Prosecuting Attorneys in a Democracy – A California Perspective - McKinley, Patrick (Review of European and Comparative Law, 2020)
A prosecuting attorney in a democracy is very important in the processing of criminal cases- from pre-filing to final appeal. Much of the involvement of the District Attorney, both before a criminal case is filed, and during the prosecution of the case, stems from the “Exclusionary Rule”. It is the usual case that the police will bring their investigation, their arrest warrant or search warrant affidavit to a District Attorney to review it prior to taking it to the judge. In this connection, District Attorneys will themselves reject 5-10% of the warrant requests submitted to them for approval, often asking law enforcement to do some further investigation before resubmitting the warrant. Furthermore, because of the Doctrine of Separation of Powers, only the District Attorney or the California State Attorney General can make the decision to file or not file a case. This Article illustrates the impact of such discretion. The problem of democracy is strictly connected to the process of DA’s selection, what has also been here presented. Another fundamental issue is a role of DA in voir dire, mainly because jury trials are guaranteed by the federal Constitution and are associated with the idea of democracy. Separation of Powers and Judicial Control of the DA, the police, and the sentencing of those convicted of crimes have been analyzed from the perspective of the California law. Additionally, the article includes final comments on the technological progress and its impact on criminal law and democracy. All the conclusions have been made in reference to Author’s experience as Assistant DA in California.